2008
DOI: 10.1186/ar2349
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Sox9 activity by crosstalk with nuclear factor-κB and retinoic acid receptors

Abstract: Introduction Sox9 and p300 cooperate to induce expression of cartilage-specific matrix proteins, including type II collagen, aggrecan and link protein. Tumour necrosis factor (TNF)-α, found in arthritic joints, activates nuclear factor-κB (NF-κB), whereas retinoic acid receptors (RARs) are activated by retinoid agonists, including all-trans retinoic acid (atRA). Like Sox9, the activity of NF-κB and RARs depends upon their association with p300. Separately, both TNF-α and atRA suppress cartilage matrix gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…Retinoic acid pretreatment significantly inhibited the NF-κB DNA binding activity both in vivo and in vitro in this study. The result was consistent with a previous study, conducted in primary cultured rat chondrocytes in which atRA reduced NF-κB activity and DNA binding [17]. Datta et al also reported that atRA reduced nuclear levels of both subunits (p50 and p65) of NF-κB in cytokine-stimulated murine mesangial cells [39].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Retinoic acid pretreatment significantly inhibited the NF-κB DNA binding activity both in vivo and in vitro in this study. The result was consistent with a previous study, conducted in primary cultured rat chondrocytes in which atRA reduced NF-κB activity and DNA binding [17]. Datta et al also reported that atRA reduced nuclear levels of both subunits (p50 and p65) of NF-κB in cytokine-stimulated murine mesangial cells [39].…”
Section: Discussionsupporting
confidence: 90%
“…Datta et al also reported that atRA reduced nuclear levels of both subunits (p50 and p65) of NF-κB in cytokine-stimulated murine mesangial cells [39]. Rockel et al reported that an antibody against retinoic acid receptor (RAR)-α interfered with binding of the of NF-κB and DNA complex, suggesting that atRA-activated RARs limit its availability for activation of NF-κB [17]. Retinoic acid directly penetrates the cell membrane and enters the nucleus to inhibit NF-κB DNA binding activity and potentially provide a feedback inhibition mechanism to terminate TLR4 downstream signalling events [40].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…16,17 Also, reciprocal interactions between RARs and nuclear factor kappaB (NFκB) has been shown, which can be of relevance when designing retinoids for chemo-preventive and anti-inflammatory interventions. 18,19 NFκB transactivation of target genes requires that heterodimers are formed between class I NFκB proteins (p105/p50 and p100/p52) and class II proteins (RelA, RelB and c-Rel), although some homodimer combinations also are reported to activate gene transcription. 20 It is important to note that the antagonistic effects performed by retinoids on AP-1 and NFκB activity do not require RAREs in the target genes.…”
mentioning
confidence: 99%
“…1) We recently also disclosed that cyclophosphamide (CP) could improve myocardial function in rats after ischemia reperfusion injury. These findings could help to gain some insight into therapeutic potential of CP in myocardial I/R injury.…”
mentioning
confidence: 99%